Assessment of polyethersulfone and polyacrylonitrile hemodialysis clinical membranes: In situ synchrotron-based imaging of human serum proteins adsorption, interaction analyses, molecular docking and clinical inflammatory biomarkers investigations. (December 2021) - Saadati, Shaghayegh; Eduok, Ubong; Westphalen, Heloisa; Abdelrasoul, Amira; Shoker, Ahmed; Choi, Phillip; Doan, Huu; Ein-Mozaffari, Farhad; Zhu, Ning
Abstract: While hemodialysis augments the physiological functions of the kidney in end stage renal disease (ESRD) patients, inherent membrane properties initiate life-threating biological episodes upon contact with blood. Membrane materials have different morphological and chemical properties that may become complement, leukocyte and even coagulation activators leading to several cardiovascular diseases due to biocompatibility issues upon contact with blood. The present study offers an in-depth understanding into two commonly used clinical polyethersulfone (PES) and polyacrylonitrile (PAN) membranes in Canadian hospitals and the effects of blood-membrane interactions on their biocompatibility, in terms of the initiation of blood activation and pro-inflammatory cytokine, from both experimental and theoretical standpoints. PES and PAN were thoroughly investigated to explore their susceptibility toward interaction with three human serum proteins. The extent of protein adsorption, and subsequent interactions on the membrane surfaces were investigated after ultrafiltration with human serum albumin (ALB), fibrinogen (FB) and transferrin (TR) proteins. The buildup of protein microparticles across different stratified membrane layers was probed using Synchrotron-based X-ray microtomography conducted with a biomedical imaging and therapy (BMIT 05ID-2) beamline at the Canada's national synchrotron light source facility. Furthermore, evidence of protein adhesion has been exhaustively investigated by surface chemical analyses and high-resolution surface imaging. The difference tendencies toward protein membrane-surface adhesion for both materials contributed to biological activations when studying in vitro clinical tests with inflammatory biomarkers using Human Magnetic Luminex assays of Serpin/ Antithrombin-III, Properdin, C5a, 1L-1α, 1L-1β, TNF-α, IL6, and vWF. Experimental results have been complemented with Molecular Modeling Docking analyses in the assessment of interaction patterns of human serum proteins in a view to understanding the relationship between functional group chemistry and membrane-surface bonding. Our models reveal inherent binding between PAN nitrogen atoms and protein-bound amino acids while the PES model proposes a contribution with its sulfone chemical groups as a prerequisite to membrane-surface binding resulting in high levels of complement and inflammation factors. The differences in protein adhesion between both clinical membrane modules are attributed to varying degrees of surface hydrophilicity as a direct factor of protein/membrane biocompatibility. Both membranes interacted differently with ALB, FB and TR, however, PAN membrane exhibited less affinity for protein adsorption and membrane-surface fouling. Graphical Abstract: ga1 Highlights: Assessment of hemodialysis using common clinical PES and PAN membranes. Both membranes interacted differently with three model human serum proteins. PAN membrane has less affinity for protein adsorption and membrane-surface fouling. SR-µCT showed a reduced protein adsorption layer by layer in PAN membrane matrices. Molecular docking indicated sulfone functional groups of PES play a key role in protein adsorption. PES hemodialysis membrane classified as strong coagulation activators compared to PAN.